Factors associated with cholestasis in newborns with gastroschisis - Juliana Zoboli Del Bigio; Ana Cristina Aoun Tannuri; Mário Cícero Falcão; Felipe Yu Matsushita; Werther Brunow de Carvalho (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: To describe the incidence and to analyze risk factors associated with cholestasis in neonates with gastroschisis. Methods: This is a retrospective cohort study in a tertiary single center analyzing 181 newborns with gastroschisis between 2009 and 2020. The following risk factors associated with cholestasis were analyzed: gestational age, birth weight, type of gastroschisis, silo closure or immediate closure, days of parenteral nutrition, type of lipid emulsion, days of fasting, days to reach a full diet, days with central venous catheter, presence of infections, and outcomes. Results: Among the 176 patients evaluated, 41 (23.3%) evolved with cholestasis. In the univariate analysis, low birth weight (p=0.023), prematurity (p<0.001), lipid emulsion with medium-chain triglycerides and long-chain triglycerides (p=0.001) and death (p<0.001) were associated with cholestasis. In the multivariate analysis, patients who received lipid emulsion with fish oil instead of medium chain triglycerides/long chain triglycerides (MCT/LCT) emulsion had a lower risk of cholestasis. Conclusions: Our study shows that lipid emulsion with fish oil is associated with a lower risk of cholestasis in neonates with gastroschisis. However, this is a retrospective study and a prospective study should be performed to confirm the results.